The Bosnian European membership deadlock - A Brussels’ credibility crisis - Brljavac, Bedrudin (Faculty of Social Sciences and Humanities, UKM,Bangi, 2011)
Bosnia and Herzegovina (BiH)’s quest for the membership of the European Union has lingered for the past 14 years with little promise of success. The main reason for this predicament has often been attributed to the chronic ethnic politics characteristics of the Bosnian country. This paper, however, takes a different view of the problem by bringing into focus the EU’s contribution to it. Four facets of the EU shortcomings were examined to prove this point, namely (1) The problem with the EU's Special Representative; (2) The problem with the EU's Stabilisation and Association Agreement in Bosnia; (3) The disunity of the European Union position on Bosnia; and (4)The failure of ‘Dayton II’. The paper concludes that the four areas of weakness point to the reality of a serious credibility crisis resulting from the capability-expectations gap on the part of the EU , a situation that had since rendered the EU ineffective in helping Bosnia and Herzegovina (BiH) to overcome its intricate domestic challenges and to bring it closer to its membership of the EU.